Speed-Testing in Audio Engineering Education: An Imperative Assessment Tool - Barry G Atticks (Journal of the Association for Technology in Music Instruction, 2024)
Multiple choice tests, fill-in the blanks, and essay question assessments do have their place in academia, but for students preparing for careers as studio engineers, live engineers, and producers, other assessments that test readiness for troubleshooting “real-world” problems in audio technology are needed. Being able to quickly solve signal flow issues is crucial whether it is for a high paying client in the studio or a rock band during a live show for 10,000 fans. It is well-documented that experiential learning is key in audio education, but I argue that it is not just the ability to complete hands-on tasks correctly but being able to do it as efficiently and at the fastest speed possible. Because learning how to handle pressure in the fast paced live and studio audio worlds is crucial for success, this paper focuses on the “need for speed” in audio education training. I will present selective interviews from new employees in the live audio field, employers in the live audio field, and studio owners who support speed-testing as an invaluable and necessary—if often neglected— assessment tool for career preparation. This paper will also address speed-testing online and future studies that may utilize virtual reality testing.